2020
DOI: 10.5217/ir.2020.00032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management for small bowel of Crohn’s disease in the treat-to-target era: now is the time to optimize treatment based on the dominant lesion

Abstract: A treat-to-target strategy, in which treatment is continuously adjusted according to the results of scheduled objective monitoring, is optimal for patients with Crohn’s disease (CD) in the era of biologics. The small bowel is a common site of intractable CD, which may result from multiple strictures or expanding lesions. To improve the prognosis of patients with small bowel CD, lesions should be proactively monitored within the subclinical phase. Objective assessment of small bowel lesions is technically diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…In the present study, patients with ileal disease at diagnosis had a higher risk of bleeding compared with those with colonic disease at diagnosis, although the result did not reach statistical significance. This is in line with the results of previous studies that ileal disease is a predictor of complicated behavior[ 25 ] and surgery[ 17 , 26 , 27 ], whereas colonic disease is a predictor of a milder disease course[ 17 , 28 ]. However, other studies reported contrasting results in that bleeding was more common in patients with colonic involvement than in those with isolated small bowel disease[ 2 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, patients with ileal disease at diagnosis had a higher risk of bleeding compared with those with colonic disease at diagnosis, although the result did not reach statistical significance. This is in line with the results of previous studies that ileal disease is a predictor of complicated behavior[ 25 ] and surgery[ 17 , 26 , 27 ], whereas colonic disease is a predictor of a milder disease course[ 17 , 28 ]. However, other studies reported contrasting results in that bleeding was more common in patients with colonic involvement than in those with isolated small bowel disease[ 2 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Mucosal healing can be regarded as epithelial regeneration after injury of the intestinal lining. Mucosal healing is considered a therapeutic target of IBD [ 26 ]. To improve mucosal healing in patients with CD, additional treatment options to promote epithelial regeneration and wound healing ability should be explored and developed.…”
Section: Discussionmentioning
confidence: 99%
“… 1 As SBCD is often associated with poor clinical outcomes, such as complicated disease course, stricturing behavior, and CD-related surgery, early diagnosis and objective evaluation of small bowel lesions are essential. 2 However, the evaluation of SBCD is more difficult than that of colonic lesions because the diseased segment of most small bowel lesions is difficult to reach during conventional endoscopy, and may appear normal on a cross-sectional image. 2 , 3 Thus, the diagnosis of SBCD is challenging and often delayed.…”
mentioning
confidence: 99%
“… 2 However, the evaluation of SBCD is more difficult than that of colonic lesions because the diseased segment of most small bowel lesions is difficult to reach during conventional endoscopy, and may appear normal on a cross-sectional image. 2 , 3 Thus, the diagnosis of SBCD is challenging and often delayed.…”
mentioning
confidence: 99%
See 1 more Smart Citation